Sex Differences In Psychoeducation For Patients With Depression: A Comparison Of Frequency And Efficacy Of Psychoeducation - Tomita, Tetsu (Neuropsychiatr Dis Treat, 2019)
BACKGROUND: We aimed to reveal sex differences in depression comprehension by reanalyzing data from a previous study of patients who were administered antidepressants. METHODS: A total of 424 outpatients were enrolled in the study. Participants were provided an original self-administered questionnaire that comprised eight items: depressive symptoms, course of depression, cause of depression, treatment plan, duration of antidepressant use, how to discontinue antidepressants, side effects of antidepressants, and psychotherapy. Each item consisted of the following two questions: “Have you received an explanation from the doctor in charge?” and “How much do you understand about your treatment?” The level of patients’ comprehension of these questions was rated on a scale of 0–10 (11 anchor points). Symptoms were evaluated using the Quick Inventory for Depressive Symptomatology, Japanese version, and other scales. Patients were divided on the basis of sex, regardless of whether they were in remission. RESULTS: Compared with male patients, female patients with depression exhibited lower levels of depression and did not receive adequate psychoeducation from their physicians. While depression comprehension of female patients might not necessarily be associated with remission, male patients in remission received more explanations about depression and understood more compared with female patients. CONCLUSION: Depression comprehension of male patients might be associated with remission, and psychoeducation should be sex-oriented to improve treatment responses.